Effects of Four Hydrocolloid Binders on Paste-Feed Stability and Behavioral Acceptance by Rice Field Eels (Monopterus albus) - Nurmahraini; Zaenal Abidin; Rangga Idris Affandi (Journal of Fish Health, 2026)
Rice field eels (Monopterus albus) are economically valuable, but culture development is constrained by continued reliance on wild stocks and natural feeds. This study explored how alginate, carboxymethyl cellulose (CMC), guar gum, and carrageenan, each included at 0%, 10%, 15%, or 20%, affected the water stability of paste feed. A separate behavioral-acceptance assessment compared the control with 10% alginate, 15% CMC, 15% guar gum, and 15% carrageenan. Stability observations were conducted in triplicate. The available experimental records did not establish independent animal-level units for the acceptance assessment; therefore, acceptance outcomes are reported descriptively and should not be interpreted as confirmatory treatment effects. Water addition differed among formulations (approximately 5–20 mL), creating a confounding effect between binder treatment and moisture content. Under these conditions, feeds containing 10% guar gum or 10% carrageenan remained physically intact longer than the other tested formulations. Behavioral-response counts did not provide reliable evidence of differences among acceptance treatments. These findings are exploratory and identify guar gum and carrageenan formulations for further testing in experiments that standardize moisture content and use clearly defined, randomized, independent animal or tank replicates.